Persistent Homoclinic Orbits for a Perturbed Cubic-quinitic Nonlinear Schrodinger Equation (Journal of Partial Differential Equations, 2002)
" In this paper, the existence of homoclinic orbits, for a perturbed cubic-quintic nonlinear Schr\u00f6dinger equation with even periodic boundary conditions, under the generalized parameters conditions is established. More specifically, we combine geometric singular perturbation theory with Melnikov analysis and integrable theory to prove the persistence of homoclinic orbits."